Recurrent Multi-territorial Acute Ischemic Stroke due to Cardiac Angiosarcoma. (3rd May 2022) - Lim, Gareth Zigui; Chua, Hsieh En; Aung, Ei Mon; Seet, Ying Hao Christopher; Lin, Xuling; Chng, Soke Miang; Tan, Louis C.S.
Abstract : A 64-year-old man with hypertension, hyperlipidemia, and diabetes mellitus presented on 2 separate occasions with recurrent acute ischemic strokes in multiple vascular territories (Figure 1). Transthoracic echocardiogram revealed a 4.2 × 2.1 cm left atrial mass with heterogenous contrast enhancement on heart MRI (Figure 2). A PET scan showed corresponding avid uptake in the left atrium with widespread bone, skin, and pulmonary metastases. Left ischial bone biopsy was consistent with angiosarcoma.